Human chorionic gonadotrophin priming for fertility treatment with in vitro maturation. - Reavey, J; Vincent, K; Child, T; Granne, I (Wiley, 2016)
Background In vitro maturation (IVM) is a fertility treatment that involves the transvaginal retrieval of immature oocytes, and their subsequent maturation and fertilisation. Although the live birth rate is lower than conventional in vitro fertilisation (IVF) with ovarian stimulation, it is a useful treatment, as it avoids the risk of ovarian hyperstimulation syndrome (OHSS). Women with polycystic ovaries (PCO) or polycystic ovarian syndrome (PCOS) are at an increased risk of OHSS. Thus, IVM may be a more useful treatment in this patient group. Strategies to maximise the maturation rates of the immature oocytes are important. This review focuses on the administration of human chorionic gonadotrophin (hCG) prior to immature oocyte retrieval Objectives To determine the effectiveness and safety of hCG priming in subfertile women who are undergoing IVM treatment in the context of assisted reproduction. Search methods We searched the following electronic databases up to 29 August 2016: Cochrane Gynaecology and Fertility Group Specialised Register of controlled trials, CENTRAL, MEDLINE, Embase, PsycINFO, and CINAHL. We also searched the trial registries ClinicalTrials.gov and WHO ICTPR to identify ongoing and registered trials. We sought recently published papers not yet indexed in the major databases, and reviewed the reference lists of reviews and retrieved studies as sources of potentially relevant studies. There were no language restrictions Selection criteria We included randomised controlled trials (RCTs) that compared hCG priming with placebo or no priming in women undergoing IVM. We also included RCTs that compared different doses of hCG, or the timing of oocyte retrieval. The primary outcomes were live birth rate and miscarriage rate per woman randomised. Data collection and analysis Two review authors independently selected studies for inclusion, and with a third author, assessed risk of bias and extracted data. We contacted the original authors where data were missing. For dichotomous outcomes, we used the Mantel-Haenszel method to calculate odds ratios (OR). For continuous outcomes, we calculated the mean differences (MD) between treatment groups. We assessed statistical heterogeneity using the I² statistic. We assessed the overall quality of the evidence using GRADE methods. Main results We included four studies, with a total of 522 women, in the review. One of these studies did not report outcomes per woman randomised, and so was not included in formal analysis. Three studies investigated 10,000 units hCG priming compared to no priming. One study investigated 20,000 units hCG compared to 10,000 units hCG priming. Three studies only included women with PCOS (N = 122), while this was an exclusion criteria in the fourth study (N = 400). We rated all four studies as having an unclear risk of bias in more than one of the seven domains assessed. The quality of the evidence was low, the main limitations being lack of blinding and imprecision. When 10,000 units hCG priming was compared to no priming, we found no evidence of a difference in the live birth rates per woman randomised (OR 0.65, 95% confidence intervals (CI) 0.24 to 1.74; one RCT; N = 82; low quality evidence); miscarriage rate (OR 0.60, 95% CI 0.21 to 1.72; two RCTs; N = 282; I² statistic = 21%; low quality evidence), or clinical pregnancy rate (OR 0.52, 95% CI 0.26 to 1.03; two RCTs, N = 282, I² statistic = 0%, low quality evidence). Though inconclusive, our findings suggested that hCG may be associated with a reduction in clinical pregnancy rates; 22% of women who received no priming achieved pregnancy, while between 7% and 23% of women who received hCG priming did so. The study comparing 20,000 units hCG with 10,000 units hCG did not report sufficient data to enable us to calculate odds ratios. No studies reported on adverse events (other than miscarriage) or drug reactions. Authors' Conclusions This review found no conclusive evidence that hCG priming had an effect on live birth, pregnancy, or miscarriage rates in IVM. There was low quality evidence that suggested that hCG priming may reduce clinical pregnancy rates, however, these findings were limited by the small number of data included. As no data were available on adverse events (other than miscarriage) or on drug reactions, we could not adequately assess the safety of hCG priming. We need further evidence from well-designed RCTs before we can come to definitive conclusions about the role of hCG priming, and the optimal dose and timing.